The Effectiveness of QRIS in Non-Cash Transactions: Perceptions of Sixth-Semester Management Students at Asahan University in 2025 - Dila Mawarsi; Della Ananda; Alsyadea Alsyadea; Agung Rivaldi Samudra; Dailami Dailami; Nurun Nazmi Hayati (Journal of Research in Social Science and Humanities, 2025)
This study aims to analyse the effectiveness of using QRIS among Asahan University students, focusing on aspects of convenience, security, efficiency, and student acceptance of digital payment systems. This research uses a descriptive quantitative approach with a survey method, where data is collected through distributing questionnaires to students as respondents. The results showed that the majority of Asahan University students have used QRIS in their daily transaction activities, and generally gave positive responses to its use. Asahan University students stated that QRIS made non-cash transactions easier, and felt satisfied using it. In addition, students stated that QRIS helps reduce the risk of carrying cash, and consider this system efficient and in accordance with the needs of the times. QRIS is also considered to support a cashless lifestyle by Asahan University students. Nevertheless, there are challenges in the form of technical obstacles such as internet networks and limited understanding of some users. In addition, there are still some students who feel more comfortable using cash. Overall, this study concludes that QRIS is quite effectively used by Asahan University students as a practical, safe, and efficient digital payment tool. The findings also show that QRIS has great potential in strengthening digital financial literacy among the younger generation and encouraging the creation of a culture of non- cash transactions in the campus environmentKeywords: QRIS, Non-Cash Transactions, Effectiveness, digital payment system, Student Perception.